PENINGKATAN PENGETAHUAN DAN SIKAP GIZI SEIMBANG ANAK SEKOLAH DASAR MELALUI MEDIA PERMAINAN EDUKASI “ZIPLOCK GAMES” - Almunawa, Iqlima; Rosmana, Dadang; Priawantiputri, Witri; Mulyo, Gurid Pramintarto Eko (Jurnal Pengabdian Masyarakat Kesehatan Indonesia, 2024)
Based on the 2018 Basic Health Research Data, it was found that the prevalence of nutritional problems in School Age Children (AUS) was in the fairly high category for the short (16.9%), thin (6.8%), overweight (9.2%) and obese (10,8%). Delivery of health information to school-age children requires media that is easy to understand and attracts children's attention so that information can be conveyed properly. This study aims to determine the effect of the educational game "Ziplock Games" on knowledge and attitudes of balanced nutrition in students at UPTD SDN 1 Bank Jabar Langensari. The research design used was a quasi-experimental design with one group pre-test post-test on 36 responden consisting of students in grades IV, V and VI. Data collection is done directly using a questionnaire. The statistical tests used in this study were the T-Dependent test and the Wilcoxon test. The results of this study indicate that there is a significant difference (P value = 0.000) between knowledge and attitudes of balanced nutrition before and after the intervention.